Indira Gandhi, the crucial years, 1973-1984 - Bahl, P. N. 1933- (New Delhi Har-Anand Publications, 1994)
Political events leading to the proclamation of emergency during the reign of Indira Gandhi, former prime minster of India, narrated by her joint secretary P.N. Bahl.
Keywords: Gandhi, Indira -- 1917-1984.; India -- Politics and government -- 1973-1977.; India -- Politics and government -- 1977-.